Refining the assessment of disrupted maternal communication: Using item response models to identify central indicators of disrupted behavior. (17th December 2017) - Haltigan, John D.; Madigan, Sheri; Bronfman, Elisa; Bailey, Heidi N.; Borland-Kerr, Catherine; Mills-Koonce, Roger; Lyons-Ruth, Karlen
Abstract: The Atypical Maternal Behavior Instrument for Assessment and Classification (AMBIANCE; Bronfman, Madigan, & Lyons-Ruth, 2009–2014; Bronfman, Parsons, & Lyons-Ruth, 1992–2004) is a widely used and well-validated measure for assessing disrupted forms of caregiver responsiveness within parent–child interactions. However, it requires evaluating approximately 150 behavioral items from videotape and extensive training to code, thus making its use impractical in most clinical contexts. Accordingly, the primary aim of the current study was to identify a reduced set of behavioral indicators most central to the AMBIANCE coding system using latent-trait item response theory (IRT) models. Observed mother–infant interaction data previously coded with the AMBIANCE was pooled from laboratories in both North America and Europe ( N = 343). Using 2-parameter logistic IRT models, a reduced set of 45 AMBIANCE items was identified. Preliminary convergent and discriminant validity was evaluated in relation to classifications of maternal disrupted communication assigned using the full set of AMBIANCE indicators, to infant attachment disorganization, and to maternal sensitivity. The results supported the construct validity of the refined item set, opening the way for development of a brief screening measure for disrupted maternal communication. IRT models in clinical scale refinement and their potential for bridging clinical and research objectives in developmental psychopathology are discussed.